Forgiven : the Amish school shooting, a mother's love, and a story of remarkable grace - Roberts, Terri; Windle, Jeanette (Minneapolis, Minnesota : Bethany House Publishers, 2015)
"The mother of the man who shot many young Amish schoolgirls before taking his own life tells of the grace she's received from the Amish, the relationships she's built with the victims and their families, and the healing and forgiveness she's found"--
Keywords: Roberts, Terri; Forgiveness of sin; Forgiveness -- Religious aspects -- Christianity; Amish School Shooting, Nickel Mines, Pa., 2006.; Amish -- Pennsylvania -- Lancaster County; Amish -- Doctrines